Longitudinal, prospective cohort study of social relationships and self-rated health in the Atherosclerosis Risk in Communities (ARIC) Study cohort and ARIC/Jackson Heart Study (JHS) shared cohort - Kennedy M. Peter-Marske; Annie Green Howard; Kelly R. Evenson; Sara Jones Berkeley; Joanna Maselko; Mario Sims; Anna Kucharska-Newton; Kevin J. Sullivan; Wayne D. Rosamond (PLoS ONE, 2025)
Introduction Social isolation and low social support are associated with low self-rated health (SRH) cross-sectionally, but few studies have assessed longitudinal associations. Aims Assess the associations of isolation, support, and different types of support with SRH trajectories over 28 years. Examine 10-year changes in isolation and support and their associations with 18-year SRH trajectories. Methods The Atherosclerosis Risk in Communities (ARIC) Study and the Jackson Heart Study (JHS) are population-based prospective cohort studies with some shared participants. We included 10,855 ARIC participants (56% women, 24% Black, mean age 57 (standard deviation: 6) years) with one measure of isolation and support in ARIC (1990–1992), and a subset of 911 ARIC/JHS shared cohort participants with these measures again in JHS (2000–2004). Isolation was measured using the 10-item Lubben Social Network Scale in ARIC, and with 3 questions from the Berkman Social Network Index in JHS. Support was measured using the 16-item Interpersonal Support Evaluation List in both studies. SRH was measured annually and scored from 0–100. We used linear mixed effects models adjusted for confounders to assess these associations. Results In ARIC, high isolation was associated with lower SRH both at baseline and over follow-up, with SRH decreasing at a slightly greater rate for those with high isolation compared to low. High support was associated with greater SRH over 28 years compared to those with low support, but the rate of decline in SRH was similar. On average, over 10 years, support was stable and isolation increased in ARIC/JHS. Although confidence intervals were wide, 10-year maintenance of high/moderate support and increases in support were associated with greater SRH over time compared to decreases in support and stable low support. Conclusion Low isolation and high support at baseline and over 10 years may be positively associated with longitudinal SRH.